Influence of Glass Fibers on Mechanical Properties of Concrete with Recycled Coarse Aggregates - Ali, Babar; Qureshi, Liaqat Ali; Raza, Ali; Nawaz, Muhammad Asad; Rehman, Safi Ur; Rashid, Muhammad Usman (Civil Engineering Journal, 2019)
Despite plain cement concrete presenting inferior performance in tension and adverse environmental impacts, it is the most widely used construction material in the world. Consumption of fibers and recycled coarse aggregates (RCA) can add ductility and sustainability to concrete. In this research, two mix series (100%NCA, and 100%RCA) were prepared using four different dosages of GF (0%GF, 0.25%GF, 0.5%GF, and 0.75%GF by volume fraction).Â  Mechanical properties namely compressive strength, splitting tensile strength, and flexural strength of each concrete mixture was evaluated at the age of 28 days. The results of testing indicated that the addition of GF was very useful in enhancing the split tensile and flexural strength of both RCA and NCA concrete. Compressive strength was not highly sensitive to the addition of GF. The loss in strength that occurred due to the incorporation of RCA was reduced to a large extent upon the inclusion of GF. GF caused significant improvements in the split tensile and flexural strength of RCA concrete. Optimum dosage of GF was determined to be 0.25% for NCA, and 0.5% for RCA concrete respectively, based on the results of combined mechanical performance (MP).